Up-regulation of human immune system function by Donkey’s Milk - Taghiloo, Saeid; Allahmoradi, Esmaeil; Sadeghian-Kiadehi, Seyedeh Forough; Omrani-Nava, Versa; Nazar, Eisa; Ebrahimzadeh, Mohammad Ali (Brazilian Journal of Pharmaceutical Sciences, 2020)
Donkey’s milk represents a good alternative to human milk because of its chemical characteristics similar to those of human’s. In present study, the pro- and anti-inflammatory effects of donkey’s milk were evaluated on peripheral blood mononuclear cells (PBMCs). PBMCs were isolated from 12 young and 12 aged normal subjects. PBMCs were cultured with or without the optimal and non-cytotoxic dose of pasteurized donkey’s milk, and polymyxin B was used to inhibit the possible endotoxin contamination. Following 18 hours incubation, culture supernatants were harvested to measure the secreted Tumor necrosis factor-α (TNF-α), Interleukin-6 (IL-6), Interleukin-8 (IL-8) and Interleukin-10 (IL-10) by ELISA. Donkey’s milk significantly increased TNF-α (p= 0.01), IL-8 (p< 0.0001), IL-6 (p< 0.0001) and IL-10 (p= 0.01) levels in PBMCs. In addition, the levels of IL-6 (p= 0.002), IL-8 (p= 0.002) and TNF-α (p= 0.002) from aged subjects were significantly higher compared with young subjects. In contrast with these data, the level of IL-10 was markedly reduced from aged subjects (p= 0.02). Considering the immune-potentiation effects of donkey’s milk, it is suggested investigating milk as a beneficial dietary component for up-regulating the immune response in aged people.